The effect of utilitarian and hedonic motivations on mobile shopping outcomes. A cross‐cultural analysis. (26th September 2022) - Hu, Lala; Filieri, Raffaele; Acikgoz, Fulya; Zollo, Lamberto; Rialti, Riccardo
Abstract: Mobile devices are ubiquitous in the lives of modern consumers, who use them for information‐seeking and purchasing activities, fostering the emergence of m‐commerce. This trend has been exacerbated by the COVID‐19 pandemic, which has boosted m‐commerce growth in both developed and developing countries. Hence, there is a need for cross‐cultural research concerning the factors affecting behavioural intentions. Drawing upon the hedonic information systems model, we measure the impact of utilitarian factors on satisfaction, repurchase intention, and eWOM through the mediation of enjoyment across two countries characterized by different stages of m‐commerce readiness and culture: China and Italy. Findings suggest that the impact of utilitarian factors on satisfaction is stronger among Italian users than Chinese users. On the contrary, for Chinese users, who use their mobile phones as a primary device to shop online, the mediation effect of enjoyment on satisfaction and eWOM is stronger. With this study, we contribute to cross‐cultural research in m‐commerce and provide guidelines to mobile retailers operating in diverse international markets.